2020
DOI: 10.1186/s13047-020-00406-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and bacteriological profile of diabetic foot infections in a tertiary care

Abstract: Background: Diabetic foot infection is a worldwide health problem is commonly encountered in daily practice. This study was conducted to identify the microbiological profile and antibiotic sensitivity patterns of causative agents identified from diabetic foot infections (DFIs). In addition, the assessment included probable risk factors contributing to infection of ulcers that harbour multidrug-resistant organisms (MDROs) and their outcomes. Methods: We carried out a prospective analysis based on the DFI sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 27 publications
3
35
0
6
Order By: Relevance
“…In Malaysia, it was concluded that Pseudomonas aeruginosa (19%), Staphylococcus aureus (11%) and bacteroides species (8%) were isolated from diabetic foot infections 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Malaysia, it was concluded that Pseudomonas aeruginosa (19%), Staphylococcus aureus (11%) and bacteroides species (8%) were isolated from diabetic foot infections 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites of infection in diabetic patients are the skin and urinary tract. Malignant or necrotizing otitis externa principally occurs in diabetic patients older than 35 years and is almost due to Pseudomonas aeruginosa 1 . Diabetic foot ulcers is a common complication of diabetes and frequently associated with the presence of Staphylococcus aureus 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Silver is a natural antibacterial agent that has been medically confirmed to destroy most bacteria that trigger foot odor and other sweaty foot issues [61]. Silver ions are released from the silver fibers and bond with the DNA chains of odor-producing bacteria [64]. By targeting the bacterial membrane, AgNPs destabilize plasma membrane potential and deplete levels of intercellular adenosine triphosphate, resulting in bacterial cell death.…”
Section: Magical Socks Nano-technology With Silver-nanoparticles (Agnps)mentioning
confidence: 99%
“…Diabetes mellitus represents major health problem worldwide with diabetic foot infections being the most common complication necessitating hospital admissions. [ 1 ] The severe forms of diabetic foot infections are polymicrobial in nature with involvement of both aerobic ( Klebsiella spp., Escherichia coli , and Staphylococcus aureus ) and anaerobic ( Bacteroides spp. and anaerobic streptococci) microflora.…”
Section: Introductionmentioning
confidence: 99%
“…and anaerobic streptococci) microflora. [ 1 ] The genus Bacteroides consist of Gram-negative, nonsporing anaerobic rods that form the integral part of the colonic microflora in humans. Bacteroides spp.…”
Section: Introductionmentioning
confidence: 99%